THE IMPACTS OF THE PANDEMIC ON PRENATAL CARE: AN INTEGRATIVE REVIEW - Batista Pereira, Janneines; do Nascimento Andrade Feitosa, Ankilma; Dantas de Lucena, Jalles; de Lira Silva, Macerlane (Health and Society, 2023)
Introduction: Prenatal care aims to identify patients at higher risk of adverse evolution and welcome the woman from the beginning of pregnancy. In 2020, the planet is heading towards a health and humanitarian crisis that the world has already experienced, and by assessing the human species under various conditions, we find ourselves facing the Covid-19 pandemic. Service disruptions and fear of going to health centers can also severely impact pregnant women and their quality of life. Objective: understand the main changes in prenatal care in primary care during the Covid-19 pandemic period, as well as promote a literature survey on the classification used by health professionals when prioritizing pregnant women; understand through the reading of articles selected for the production of the work, the protocols adopted during the assistance to combat Covid-19. Method: To produce a research of integrative review being based on the experience lived by the author in the context of the realization of an integrative review, having as a guiding question the prenatal care in the period of the Covid-19 pandemic in the neighborhood of Nossa Senhora de Fátima in the city of Conceição-PB. Results and discussion: The research selected articles and news about the topic as a theoretical basis. Thus, it included articles from authors who best treated the theme proposed in the work as ESTRELA (2021); MAGGE (2020) and MARQUES (2020). Conclusion: shows the importance of guidance, adequate information and knowledge about the management of pregnant women during a pandemic and the management of people to avoid proper infection by COVID-19, however, there are somewhat restricted publications and conclusive studies that can assist nursing. It is worth mentioning that it requires dynamic and comprehensive attention to reduce and/or concentrate